Analisis Pola Penjualan Alat-Alat Kesehatan Menggunakan Algoritma Apriori Pada PT. Dian Fajar Cahaya Gemilang - badrul; Ahmat Eka Saputra; Abas Wahyudi; Siti Arum Fauziah (Universitas Putera Batam, 2025)
PT. Dian Fajar Cahaya Gemilang is a company engaged in the sale of medical equipment. To improve the quality of service to consumers, the company is required to be able to overcome problems that often arise, including changes in order requests for certain products so that the company cannot provide product stock quickly and accurately. Lack of stock in a company will have a very negative impact on the success and smoothness of sales and purchase transactions. This can be caused by customer sales patterns that are always changing and cannot be predicted. This study implements data mining using the apriori algorithm stage to find valuable information in the form of purchasing patterns by customers by utilizing the large amount of sales transaction data so that the company can prepare stock quickly and accurately to prevent accumulation and lack of product storage that will later result in losses